Associations between common variants in iron-related genes with haematological traits in populations of African ancestry - Gichohi-Wainaina, Wanjiku N.; Tanaka, Toshiko; Towers, G. Wayne; Verhoef, Hans; Veenemans, Jacobien; Talsma, Elise F.; Harryvan, Jan; Boekschoten, Mark V.; Feskens, Edith J.M.; Melse-Boonstra, Alida (Public Library of Science, 2016)
Background Large genome-wide association (GWA) studies of European ancestry individuals have identified multiple genetic variants influencing iron status. Studies on the generalizability of these associations to African ancestry populations have been limited. These studies are important given interethnic differences in iron status and the disproportionate burden of iron deficiency among African ancestry populations. Methods We tested the associations of 20 previously identified iron status-associated single nucleotide polymorphisms (SNPs) in 628 Kenyans, 609 Tanzanians, 608 South Africans and 228 African Americans. In each study, we examined the associations present between 20 SNPs with ferritin and haemoglobin, adjusting for age, sex and CRP levels. Results In the meta analysis including all 4 African ancestry cohorts, we replicated previously reported associations with lowered haemoglobin concentrations for rs2413450 (β = -0.19, P = 0.02) and rs4820268 (β = -0.16, P = 0.04) in TMPRSS6. An association with increased ferritin concentrations was also confirmed for rs1867504 in TF (β = 1.04, P = <0.0001) in the meta analysis including the African cohorts only. Conclusions In all meta analyses, we only replicated 4 of the 20 single nucleotide polymorphisms reported to be associated with iron status in large GWA studies of European ancestry individuals. While there is now evidence for the associations of a number of genetic variants with iron status in both European and African ancestry populations, the considerable lack of concordance highlights the importance of continued ancestry-specific studies to elucidate the genetic underpinnings of iron status in ethnically diverse populations.